2011
DOI: 10.1111/j.1749-6632.2011.06169.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there any sense in the Palisade endings of eye muscles?

Abstract: Palisade endings (PEs), which are unique to the eye muscles, are associated with multiply innervated muscle fibers. They lie at the myotendinous junctions and form a cap around the muscle fiber tip. They are found in all animals investigated so far, but their function is not known. Recently, we demonstrated that cell bodies of PEs and tendon organs lie around the periphery of the oculomotor nucleus in the C- and S-groups. A morphological analysis of these peripheral neurons revealed the existence of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…One of the features of the MIFs in the global layer is the presence of palisade endings where they insert into the tendon. Although these have long been considered to be proprioceptors (Billig et al, ; Büttner‐Ennever and Horn, ; Donaldson, ; Eberhorn et al, ; Lienbacher and Horn, ; Lienbacher et al, ; Ruskell et al, ; Steinbach, ; Weir et al, ), the axons giving rise to the palisade endings also display motor features (Eberhorn et al, ; Konakci et al, ; Rungaldier et al, ). Recent evidence from cats and monkeys indicates that these palisade endings originate from MIF motoneurons, and they have been reported to be extensions of the axon supplying the MIF (Büttner‐Ennever et al, ; Konakci et al, ; Zimmermann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the features of the MIFs in the global layer is the presence of palisade endings where they insert into the tendon. Although these have long been considered to be proprioceptors (Billig et al, ; Büttner‐Ennever and Horn, ; Donaldson, ; Eberhorn et al, ; Lienbacher and Horn, ; Lienbacher et al, ; Ruskell et al, ; Steinbach, ; Weir et al, ), the axons giving rise to the palisade endings also display motor features (Eberhorn et al, ; Konakci et al, ; Rungaldier et al, ). Recent evidence from cats and monkeys indicates that these palisade endings originate from MIF motoneurons, and they have been reported to be extensions of the axon supplying the MIF (Büttner‐Ennever et al, ; Konakci et al, ; Zimmermann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, bats are known to provide a range of valuable ecosystem services [82], including reducing the numbers of insect pests [83,84]. We found that Noctuidae was the most frequently encountered lepidopteran family represented mainly by the square spot rustic, X. xanthographa, which were identified in 80.6% of the pellets in the molecular analysis, and the large yellow underwing, Noctua pronuba, which were found in 63% of the pellets in the molecular analysis .…”
Section: Discussionmentioning
confidence: 99%
“…Although for many years, palisade endings were considered proprioceptive (Donaldson 2000), there is some dispute about this. The nuclei of the nerves originating in the palisade endings lie in the oculomotor nucleus and travel in the oculomotor nerve (Lienbacher et al 2011). They originate in a part of the nucleus known to innervate nontwitch, multiply innervated muscle fibers (Lienbacher & Horn 2012).…”
Section: The Peripheral Source Of the Eye Position Signalmentioning
confidence: 99%